Loss of heterozygosity on chromosomes 17 and 18 in breast carcinoma: two additional regions identified. - Cropp, C S (1990)
The loss of heterozygosity (LOH) at specific regions of the human genome in tumor DNA is recognized as evidence for a tumor-suppressor gene located within the corresponding region of the homologous chromosome. Restriction fragment length polymorphism analysis of a panel of primary human breast tumor DNAs has led to the identification of two additional regions on chromosomes 17q and 18q that frequently are affected by LOH. Deletions of each of these regions have a significant correlation with clinical parameters that are associated with aggressive breast carcinomas. Previous restriction fragment length polymorphism analysis of this panel of tumors has uncovered several other frequently occurring mutations. LOH on chromosome 18q frequently occurs in tumors with concomitant LOH of loci on chromosomes 17p and 11p. Similarly, tumors having LOH on 17q also have LOH on chromosomes 1p and 3p. This suggests that certain combinations of mutations may collaborate in the development and malignant progression of breast carcinomas.